Delayed-Onset Neuropathic Pain after Septoplasty. (22nd December 2021) - Koumpa, Foteini-Stefania; Ferguson, Mark; Saleh, Hesham
Abstract : Postoperative pain following a septoplasty is expected to be mild and limited to a few days after the operation. Chronic pain following the procedure is rare. No cases of delayed-onset neuropathic pain or allodynia have been described in the literature. This paper presents a case of delayed-onset neuropathic pain after septoplasty in a previously pain-free asthmatic patient that was successfully managed by administration of intranasal local anaesthesia. Physical examination and imaging excluded any other cause of neuralgia. A literature review revealed reports of chronic pain in patients following septoplasty if there were nasal contact or compression points or nasal tumours. Separately, acute postseptoplasty allodynia is documented in iatrogenic maxillary nerve damage. However, delayed-onset neuralgic pain, exacerbated by certain environmental triggers, has not been previously described. Facial pain can be debilitating; successfully managing this neuralgic pain with administration of intranasal local anaesthetic had a substantial effect on the patient's quality of life.